104k views
5 votes
Prove the above question and i will give you....​

Prove the above question and i will give you....​-example-1
User Domandinho
by
6.0k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

Using the identity

cos²A - sin²B = cos(A + B) . cos(A - B)

Here A =
(\pi )/(8) +
(A)/(2) , B =
(\pi )/(8) -
(A)/(2)

Consider the left side

cos²(
(\pi )/(8) +
(A)/(2) ) - sin²(
(\pi )/(8) -
(A)/(2) )

= cos(
(\pi )/(8) +
(A)/(2) +
(\pi )/(8) -
(A)/(2) ) × cos(
(\pi )/(8) +
(A)/(2) -
(\pi )/(8) +
(A)/(2) )

= cos (
(\pi )/(4) ) × cos ( A)

=
(1)/(√(2) ) cosA

= right side , thus proven

User Simon Klee
by
6.2k points